BOShLANGʻICh SINF OʻQUVChILARNING TANQIDIY FIKRLASh KOʻNIKMALARINI ShAKLLANTIRISh - Saburov, D.B. (SCIENCE and SOCIETY, 2025)
The topic of the formation of critical thinking skills of younger schoolchildren by means of oral folk art explores the importance of oral folk art in the development of students’ thinking abilities.